Digital Telepressure and Employee Well-being in the Remote Work Era: The Mediating Role of Work-Life Balance. - Adeseko Sunday Olaifa; Afusat Titilayo Alabi (HARAMAIN: Jurnal Manajemen Bisnis, 2025)
The rapid expansion of remote work and digitally mediated communication has intensified concerns regarding employee well-being in contemporary organizations. One of the most prominent challenges in this context is digital telepressure, defined as the psychological urge to respond promptly to work-related messages through digital communication channels. This study examines the effect of digital telepressure on employee well-being, with work-life balance serving as a mediating variable, in the context of PT Nippon Indosari Corpindo Tbk. A quantitative explanatory design was employed using data collected from 65 employees through a structured questionnaire. The data were analyzed using SPSS version 25, including classical assumption tests, multiple linear regression, path analysis, and the Sobel test to examine the mediating effect. The findings reveal that digital telepressure has a negative and significant effect on employee well-being and also negatively affects work-life balance. In contrast, work-life balance has a positive and significant effect on employee well-being. The path analysis confirms that work-life balance significantly mediates the relationship between digital telepressure and employee well-being, indicating that the negative influence of telepressure on well-being occurs both directly and indirectly through reduced balance between work and personal life. These findings contribute to the literature by clarifying the behavioral mechanism linking digital communication pressure to employee well-being in the remote work era. Practically, the study suggests that organizations should establish healthier digital communication norms, protect employees’ non-work time, and strengthen work-life balance policies to support sustainable well-being and performance.